Educação a distância no contexto da Educação Especial: Inclusão de pessoas com deficiência nos cursos de graduação a distância da Universidade Federal do Maranhão - NUNES, Paula Estrela da Silva (2023)
The general objective of this study was to analyze the process of inclusion and permanence of students with disabilities in distance learning undergraduate courses at the Federal University of Maranhão (UFMA), taking into account the conception of the pole coordinators, within the Open University of Brazil (UAB), in order to identify the limits and possibilities to think about the creation of actions and services that can expand the access of these students in the university. Thus, the methodological path of the research was an exploratory, descriptive research, with a qualitative approach, with a survey of the existing poles at UFMA, to identify the coordinators of the distance undergraduate courses, and subsequent verification of the conditions that facilitate or hinder the permanence of students with disabilities in undergraduate courses at UFMA. Six pole coordinators from the cities of Açailândia, Codó, Coelho Neto, Fortaleza das Nogueiras, Nina Rodrigues and São Luís (Bacanga) participated in the study. In this sense, the study occurred in two stages, the first at the beginning of the year 2022, which proceeded with the exploratory phase to survey the number of UAB/UFMA centers, undergraduate courses offered in each city, number of center coordinators and number of distance undergraduate courses. The second stage occurred in the second half of 2022 and early 2023, in which questionnaires were sent to the 35 existing pole coordinators, in order to identify the inclusion of students with disabilities, with active enrollment and in order to analyze factors that favor or not this inclusion. The data collected occurred through the application of a questionnaire with semi-structured questions sent by e-mail and through the Whatsapp application. From the information obtained it was possible to verify, through the conception of the research participants, that the student with disabilities has the right to access the university guaranteed. In relation to their permanence, there is a need to expand the physical structure of the poles, human and technological resources to better develop the skills and autonomy of these students, aiming to contemplate in a more comprehensive way the accessibility and guarantees through the services offered by UFMA.